Characteristics of Membranes Derived from Pineapple Biowaste: The Effect of Nanoclay Addition - Cinta Aulia Sari , Nanda Lidya; Aminnudin, Aminnudin; Suryanto, Heru; Binoj, Joseph Selvi; Bright, Brailson Mansingh; Jatisukamto, Gaguk; Wijaya, Husni Wahyu; Osman, Azlin Fazlina; Yanuhar, Uun (Applied Science and Engineering Progress, 2026)
Indonesia, a major pineapple producer, generates substantial biowaste that can harm the ecosystem. To address this, bacterial cellulose (BC) was produced through microbial fermentation of pineapple peel waste. The study aims to evaluate the properties of BC after it has been reinforced with nanoclay. Methods include cellulose synthesis via fermentation with pineapple biowaste extract, followed by cellulose alkalization, defibrillation, and the synthesis of bacterial cellulose with nanoclay concentrations of 2, 4, 6, and 8 wt.%, which is then dried to form a solid membrane. SEM, XRD, FTIR, tensile testing, antibacterial activity, and porosity analysis were used to characterize the samples. The results show that nanoclay has a considerable influence on the surface morphology of cellulose composites. XRD analysis confirmed that nanoclay incorporation disrupted the BC crystalline structure, reducing crystallinity as nanoclay content increased. Furthermore, nanoclay reduces the membrane’s crystallinity index to 75.3% at 8 wt.% nanoclay concentration, FTIR analysis revealed changes in functional groups, indicating strong interactions between BC and nanoclay. Although tensile strength decreased with higher nanoclay content, membrane porosity improved at 6 wt.%, enhancing membrane permeability. Antibacterial testing showed significant inhibition of E. coli and S. aureus, with the highest activity observed at 8 wt.% nanoclay.